Web-based Real-Time Inventory Information System Design: An Operational Efficiency Solution at PT. Visual Media Creative - Stiawan, Fengky; Rahmanto, Yuri (Sistemasi: Jurnal Sistem Informasi, 2025)
This study developed a web-based real-time inventory information system to address delays in data processing and the high potential for recording errors at PT Visual Media Creative, which previously relied on conventional methods using books and MS Excel. The system was designed using a prototyping method with an iterative and participatory approach, involving stages of user requirements analysis, interface design, implementation with the CodeIgniter framework and MySQL, and testing. Black-box testing was applied to verify functional compliance, while usability testing involved six internal respondents to evaluate ease of use. The results showed that all functions operated according to specifications with a 100% success rate, and usability testing received positive feedback from respondents. The system implementation reduced inventory report management time from 4–8 hours to 1–2 hours per day, decreased input errors by up to 75%, and accelerated data retrieval from approximately 3 minutes to less than 10 seconds. The contribution of this research lies in providing an integrated, real-time data-driven solution that enhances operational efficiency, improves data accuracy, and supports decision-making within the company.